Identification of β-Dystrobrevin as a Direct Target of miR-143: Involvement in Early Stages of Neural Differentiation. - Maria Teresa Quaranta; Isabella Spinello; Rosa Paolillo; Gianfranco Macchia; Alessandra Boe; Marina Ceccarini; Catherine Labbaye; Pompeo Macioce (PLoS ONE)
Duchenne Muscular Dystrophy, a genetic disorder that results in a gradual breakdown of muscle, is associated to mild to severe cognitive impairment in about one-third of dystrophic patients. The brain dysfunction is independent of the muscular pathology, occurs early, and is most likely due to defects in the assembly of the Dystrophin-associated Protein Complex (DPC) during embryogenesis. We have recently described the interaction of the DPC component β-dystrobrevin with members of complexes that regulate chromatin dynamics, and suggested that β-dystrobrevin may play a role in the initiation of neuronal differentiation. Since oxygen concentrations and miRNAs appear as well to be involved in the cellular processes related to neuronal development, we have studied how these factors act on β-dystrobrevin and investigated the possibility of their functional interplay using the NTera-2 cell line, a well-established model for studying neurogenesis. We followed the pattern of expression and regulation of β-dystrobrevin during the early stages of neuronal differentiation induced by exposure to retinoic acid (RA) under hypoxia as compared with normoxia, and found that β-dystrobrevin expression is regulated during RA-induced differentiation of NTera-2 cells. We also found that β-dystrobrevin pattern is delayed under hypoxic conditions, together with a delay in the differentiation and an increase in the proliferation rate of cells. We identified miRNA-143 as a direct regulator of β-dystrobrevin expression, demonstrated that β-dystrobrevin is expressed in the nucleus and showed that, in line with our previous in vitro results, β-dystrobrevin is a repressor of synapsin I in live cells. Altogether the newly identified regulatory pathway miR-143/β-dystrobrevin/synapsin I provides novel insights into the functions of β-dystrobrevin and opens up new perspectives for elucidating the molecular mechanisms underlying the neuronal involvement in muscular dystrophy.